2001
DOI: 10.2165/00128072-200103010-00004
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppressive Drugs in Paediatric Liver Transplantation

Abstract: Orthotopic liver transplantation is established treatment for children with acute and chronic liver failure. Despite advances in pre- and postoperative management, innovative surgical techniques and new immunosuppressive drugs, acute and chronic rejection remains a problem. In addition, well established adverse effects of commonly used immunosuppressive drugs are no longer accept able. More potent, but less toxic, immunosuppressive agents have been developed and some novel compounds are now entering routine pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 131 publications
(135 reference statements)
0
15
0
Order By: Relevance
“…This T-cell inhibition proved to be effective when Dac was used in the rejection prophylaxis of patients undergoing solid organ transplant. 11,12 Dac was also found to be effective as second-line treatment of steroid-resistant GVHD in a limited number of reports that mostly referred to adult populations. [5][6][7][8][9][10] Response rates for aGVHD ranged between 29 and 68% in these series; however, data regarding the children who were included in these studies were not evaluable separately because they were not stratified by age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This T-cell inhibition proved to be effective when Dac was used in the rejection prophylaxis of patients undergoing solid organ transplant. 11,12 Dac was also found to be effective as second-line treatment of steroid-resistant GVHD in a limited number of reports that mostly referred to adult populations. [5][6][7][8][9][10] Response rates for aGVHD ranged between 29 and 68% in these series; however, data regarding the children who were included in these studies were not evaluable separately because they were not stratified by age.…”
Section: Discussionmentioning
confidence: 99%
“…In studies involving exclusively adults, or both adult and paediatric populations, [5][6][7][8][9][10] Dac is reportedly safe when used in children as rejection prophylaxis after organ transplantation, 11,12 and effective in the second-line treatment of refractory acute GVHD (aGVHD) and chronic GVHD (cGVHD).…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] Over the past decade, several studies have demonstrated a similar clinical effectiveness of MMF in paediatric transplant patients. [14][15][16] MMF has also been proven effective in autoimmune diseases in children. [17][18][19][20] Here, we report our experience with MMF in paediatric patients with autoimmune uveitis.…”
Section: Clinical Studymentioning
confidence: 99%
“…Nine of them achieved inflammation control on MMF without concomitant corticosteroids or other IMTs for a median of 15 months (range: [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. During this follow-up period, 8 out of the 9 patients experienced no uveitis relapse; 1 patient experienced one relapse that was treated with 4 weeks of topical corticosteroids.…”
Section: Treatment Outcomesmentioning
confidence: 99%
“…2 Daclizumab has been shown to be safe in children when used to prevent rejection after solid organ transplantation. 3,4 A few small studies have shown daclizumab to be effective in treating refractory acute and chronic GVHD in adults. 2,[5][6][7] Three of these studies included a small number of children; 2,6,7 however, results were not stratified by age.…”
Section: Introductionmentioning
confidence: 99%